Ly6G deficiency alters the dynamics of neutrophil recruitment and pathogen capture during Leishmania major skin infection - Corinna L. Kleinholz (Nature Portfolio, 2021)
Abstract Neutrophils represent one of the first immune cell types recruited to sites of infection, where they can control pathogens by phagocytosis and cytotoxic mechanisms. Intracellular pathogens such as Leishmania major can hijack neutrophils to establish an efficient infection. However the dynamic interactions of neutrophils with the pathogen and other cells at the site of the infection are incompletely understood. Here, we have investigated the role of Ly6G, a homolog of the human CD177 protein, which has been shown to interact with cell adhesion molecules, and serves as a bona fide marker for neutrophils in mice. We show that Ly6G deficiency decreases the initial infection rate of neutrophils recruited to the site of infection. Although the uptake of L. major by subsequently recruited monocytes was tightly linked with the concomitant uptake of neutrophil material, this process was not altered by Ly6G deficiency of the neutrophils. Instead, we observed by intravital 2-photon microscopy that Ly6G-deficient neutrophils entered the site of infection with delayed initial recruitment kinetics. Thus, we conclude that by promoting neutrophils’ ability to efficiently enter the site of infection, Ly6G contributes to the early engagement of intracellular pathogens by the immune system.